Copper nanosheet and preparation method and application thereof
By using surfactant and coordination agent for passivation and etching during the synthesis of copper nanosheets, the problem of difficult to regulate the size and thickness of copper nanosheets is solved, and the precise preparation and efficient catalytic application of ultra-thin copper nanosheets are achieved.
Patent Information
- Application Number
- CN202411711593.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing copper nanosheets have large sizes and thicker thicknesses, making it difficult to achieve precise regulation, which limits their application in catalysis, sensing and other fields.
By adding surfactant and coordination agent to the copper salt, a reduction reaction is carried out to form a nucleus, and oxidative etching is performed using an etchant. Combined with the passivation of the surfactant and coordination agent, ultra-thin copper nanosheets with controllable size are obtained.
The precise size control of copper nanosheets is achieved, and the thickness is controlled between 3 and 6 nm, which improves the stability and catalytic activity of nanosheets. It is suitable for catalytic reactions such as the reduction of 4-nitrophenol.
Smart Images

Figure CN119525512A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nanomaterials, and specifically relates to a copper nanosheet and a preparation method and application thereof. Background Art
[0002] Nanocrystals of coin metals (gold, silver, copper) have attracted much attention due to their strong localized surface plasmon resonance (LSPR) in the visible range and their unique catalytic properties. The above properties mainly depend on the size and morphology of the nanocrystals. Therefore, it is crucial to tune the optical and catalytic activities through the control of size and morphology.
[0003] Compared with precious metals gold and silver, copper is cheaper and is expected to replace gold and silver materials with better cost performance. Copper nanosheets have attracted much attention in molecular detection, carbon dioxide reduction, flexible electronics, etc. due to their anisotropy, high specific surface area, and controllable crystal planes. However, the uniformity, size adjustability, and thickness control of copper nanosheets remain an important challenge.
[0004] To this end, people have developed methods for synthesizing copper nanosheets, such as seed crystal growth and solvent thermal. For example, Gao Chuanbo's research group used precious metals platinum and palladium as seed crystals to synthesize copper nanosheets by lattice mismatch-induced defects (Small2023,2206838), but the use of precious metals significantly increased the synthesis cost; Ren et al. from the University of Buffalo synthesized copper nanosheets from the University of Buffalo by hydrothermal method (ACS Appl. Nano Mater.2022,5,4028-4037), but the size of the nanosheets was micrometer-sized and difficult to control.
[0005] The above methods have achieved some success in the synthesis of copper nanosheets. However, the existing methods are still lacking in the size control and thickness control of copper nanosheets. The thickness of the obtained copper nanosheets often exceeds 20nm, and the size is generally large and difficult to accurately control, which hinders its application in catalysis, sensing and other fields. Therefore, it is of great significance to develop a controllable synthesis method for ultra-thin copper nanosheets with controllable size.
[0006] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0007] The purpose of the present invention is to provide a copper nanosheet and a preparation method and application thereof, which solves the problem that the existing copper nanosheets are large in size and thick in thickness. The copper nanosheet of the present invention has a size of 30 to 500 nm and a thickness of 3 to 6 nm.
[0008] In order to achieve the above-mentioned object, the present invention provides a method for preparing copper nanosheets, which comprises: adding a surfactant and a ligand to a copper salt, reducing the copper salt to nuclei by a reducing agent, using the nuclei as seeds for the growth of nanocrystals, etching away non-flaky crystals during oxidation etching by an etchant, passivating the surface of the copper nanosheets with the surfactant and the ligand to protect the flaky seed crystals of copper, thereby obtaining copper nanosheets.
[0009] Preferably, the method comprises: adding a copper salt, a surfactant, a ligand and an etchant into a solvent so that the concentration of the copper salt in the reaction system is 1×10 -5 mol / L~5×10 -2 mol / L, and then heated to 20-80°C to obtain a mixed solution; adding a reducing agent to the mixed solution, stirring and reacting for 1-3 hours to obtain an ultrathin copper nanosheet; or, adding a copper salt, a surfactant and a ligand to a solvent to make the concentration of the copper salt in the reaction system be 1×10 -5 mol / L~5×10 -2 mol / L, and then heated to 20-80° C. to obtain a mixed solution; then, an etchant and a reducing agent are added to the mixed solution, and the mixture is stirred for reaction for 1-3 hours to obtain an ultrathin copper nanosheet.
[0010] Preferably, the copper salt is selected from any one or more of copper chloride, copper nitrate, copper sulfate, copper acetate, copper formate, copper acetylacetonate and copper hydroxide; or / and, the surfactant is selected from any one or more of polyvinyl pyrrolidone, hexadecyl ammonium chloride, hexadecyl ammonium bromide and polydiallyldimethylammonium chloride; or / and, the ligand is selected from any one or more of diethylamine, ethylenediamine, ethanolamine, propylenediamine, ammonia water and sodium iodide; or / and, the etchant is selected from any one or more of oxygen, hydrogen peroxide and iodine; or / and, the reducing agent is selected from any one or more of hydroxylamine, hydroxylamine hydrochloride and hydrazine hydrate.
[0011] Preferably, when the etchant is selected from oxygen, oxygen gas is bubbled in to achieve etching.
[0012] Preferably, when the oxygen is bubbled at a rate of 150 mL / min, the bubbling time is more than 5 minutes.
[0013] Preferably, the solvent is selected from any one or more of water, dimethylformamide and ethylene glycol.
[0014] Preferably, the concentration of the surfactant in the mixed solution is 1wt%; the concentration of the ligand in the mixed solution is greater than or equal to the concentration of the copper salt; the concentration of the etchant in the mixed solution is 0.1 to 2 times the concentration of the copper salt; and the concentration of the reducing agent in the mixed solution is 2 to 10 times the concentration of the copper salt.
[0015] More preferably, the concentration of the surfactant in the mixed solution is 1 wt %; the concentration of the etchant in the mixed solution is 2 to 2.5×10 -2 mol / L; the concentration of the complexing agent in the mixed solution is 5×10 -2 mol / L; the concentration of the reducing agent in the mixed solution is 0.1-0.2 mol / L.
[0016] The second object of the present invention is to provide copper nanosheets obtained by the preparation method.
[0017] Preferably, the shape of the copper nanosheets includes: triangle and / or hexagon.
[0018] The third object of the present invention is to provide the use of the copper nanosheets in reducing 4-nitrophenol to synthesize 4-aminophenol.
[0019] The copper nanosheets and the preparation method and application thereof of the present invention solve the problem that the existing copper nanosheets are large in size and thick in thickness, and have the following advantages:
[0020] The synthesis method of the present invention, by using a ligand and a surfactant, passivates the specific crystal face of the copper nanosheet and inhibits its reactivity, thereby maintaining a higher stability of the flaky nanocrystal relative to other types of seed crystals, and can effectively protect the flaky seed crystals of copper, making them more stable than non-flaky seed crystals during the oxidation etching process, and being preserved during the oxidant etching process, and due to the passivation of the ligand and the surfactant, the thickness of the nanosheet remains substantially unchanged during the growth process. In addition, by controlling the type and concentration of the added oxidant to regulate the etching process, the seed crystal concentration in the reaction system can be effectively regulated, thereby achieving size (average side length) regulation. In short, the seed crystal screening mechanism introduced by the present invention can effectively etch non-flaky materials, retain the flaky structure, achieve the purification of the copper nanosheet, and simultaneously achieve the regulation of its seed crystal concentration, thereby achieving precise size regulation. The copper nanosheet obtained by the present invention shows excellent catalytic activity in 4-NP reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the synthesis mechanism of the copper nanosheets of the present invention.
[0022] Figure 2 This is a transmission electron microscope image of the copper nanosheet prepared in Example 1 of the present invention.
[0023] Figure 3 This is a transmission electron microscope image of the copper nanosheets prepared in Example 2 of the present invention.
[0024] Figure 4This is an atomic force microscope image of the copper nanosheet prepared in Example 2 of the present invention.
[0025] Figure 5 This is an atomic force microscope image of the copper nanosheet prepared in Example 3 of the present invention.
[0026] Figure 6 This is a transmission electron microscope image of the copper nanosheet prepared in Example 4 of the present invention.
[0027] Figure 7 This is a transmission electron microscope image of the copper nanosheets prepared in Example 5 of the present invention.
[0028] Figure 8 This is a transmission electron microscope image of the copper nanosheets prepared in Example 6 of the present invention.
[0029] Fig. 9 This is a transmission electron microscope image of the copper nanosheet prepared in Comparative Example 1 of the present invention.
[0030] Fig.10 This is a spectrum diagram of the copper nanosheets prepared in Example 2 of Application Example 1 of the present invention during the catalytic process. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.
[0033] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0034] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.
[0035] Example 1
[0036] A copper nanosheet, the synthesis method of which is as follows:
[0037] Copper sulfate, polyvinyl pyrrolidone (as surfactant), iodine (as etchant) and ethylenediamine (as ligand) were added to water to make the concentration of copper salt in the system 5×10 -2 mol / L, polyvinyl pyrrolidone concentration was 1wt%, and iodine concentration was 2.5×10 -2 mol / L, ethylenediamine concentration is 5×10 -2 mol / L. Mix well and heat to 40℃.
[0038] A hydroxylamine solution (as a reducing agent) was added to the mixed solution to a concentration of 0.2 mol / L, and the mixture was stirred vigorously at 40° C. for 2 hours to obtain copper nanosheets.
[0039] like Figure 2 As shown, it is a transmission electron microscope image of the copper nanosheet prepared in Example 1 of the present invention. Figure 1 As can be seen in the figure, the average side length of the prepared nanosheets is about 30 nm, and they are mainly triangles or hexagons. The yield of the obtained copper nanosheets is 91%.
[0040] Example 2
[0041] A copper nanosheet, the synthesis method of which is substantially the same as that of Example 1, except that:
[0042] The etchant is hydrogen peroxide, and the coordination agent is ethanolamine; the concentration of hydrogen peroxide is 2×10 -2 mol / L; mix well and heat to 30℃;
[0043] The reducing agent is a hydrazine hydrate solution with a concentration of 0.1 mol / L. The solution is stirred vigorously at 30° C. for 3 hours.
[0044] like Figure 3 As shown, it is a transmission electron microscope image of the copper nanosheets prepared in Example 2 of the present invention, as shown in Figure 4 The figure shows an atomic force microscope image of the copper nanosheets prepared in Example 2 of the present invention. As can be seen from the figure, the average side length of the prepared nanosheets is about 200nm, the average thickness is 5nm, and they are mainly triangular or hexagonal. The yield of the obtained copper nanosheets is 95%.
[0045] Example 3
[0046] A copper nanosheet, the synthesis method of which is substantially the same as that of Example 2, except that:
[0047] The concentration of hydrogen peroxide is 4×10 -2 mol / L.
[0048] like Figure 5 The figure shows an atomic force microscope image of the copper nanosheets prepared in Example 3 of the present invention. As can be seen from the figure, the average side length of the prepared nanosheets is about 400nm, and the average thickness is 5nm. The yield of the obtained copper nanosheets is 97%.
[0049] It can be seen from Examples 2 and 3 that the concentration of the etchant will affect the size of the nanosheets. The greater the concentration of the etchant, the greater the average side length of the nanosheets. Therefore, the size of the nanosheets can be effectively controlled by the amount of the etchant.
[0050] Example 4
[0051] A copper nanosheet, the synthesis method of which is as follows:
[0052] Copper acetate, polyvinyl pyrrolidone (as a surfactant), and propylene diamine (as a complexing agent) were added to water to make the copper concentration in the system 1×10 -5 mol / L, the concentration of polyvinyl pyrrolidone was 1wt%, and the concentration of propylene diamine was 5×10 - 2 mol / L, after being evenly mixed, oxygen (as an etchant) was bubbled at a rate of 150 mL / min for 30 minutes, and then the mixed solution was sealed and heated to 80°C.
[0053] A mixed solution of hydroxylamine hydrochloride and hydrazine hydrate (molar ratio of 1:1) was added to the above mixed solution to make the total concentration of the reducing agent 0.1 mol / L, and the mixture was vigorously stirred and reacted at 80° C. for 1 hour to obtain copper nanosheets.
[0054] like Figure 6 The figure shows a transmission electron microscope image of the copper nanosheets prepared in Example 4 of the present invention. As can be seen from the figure, the average side length of the prepared nanosheets is about 33nm, and the average thickness is less than 5nm, so it is not easy to measure the specific average thickness. The yield of the obtained copper nanosheets is 84%.
[0055] Example 5
[0056] A copper nanosheet, the synthesis method of which is substantially the same as that of Example 4, except that:
[0057] Oxygen was bubbled at a rate of 150 mL / min for 5 minutes.
[0058] like Figure 7 The figure shows a transmission electron microscope image of the copper nanosheets prepared in Example 5 of the present invention. It can be seen from the figure that the average side length of the prepared nanosheets is about 28 nm. The yield of the obtained copper nanosheets is 61%.
[0059] It can be seen from Examples 4 and 5 that when oxygen is used as an etchant, due to its low solubility in water (8 mg / L at 20° C.), the yield of the obtained nanosheets is significantly reduced when the bubbling time is short.
[0060] Example 6
[0061] A copper nanosheet, the synthesis method of which is as follows:
[0062] Copper chloride, polyvinyl pyrrolidone (as a surfactant), sodium iodide and ethanolamine (as a complexing agent) were added to water to make the concentration of copper salt in the system 1×10 -5 mol / L, polyvinyl pyrrolidone concentration was 1wt%, sodium iodide concentration was 1×10 -5 mol / L, ethanolamine concentration is 1×10 -4 mol / L. Mix well and heat to 40℃.
[0063] Add hydrogen peroxide solution (as an etchant) and hydrazine hydrate solution (as a reducing agent) to the above mixed solution to make their concentrations 2×10 -5 mol / L and 1×10 -4 mol / L, and reacted vigorously with stirring at 20°C for 3 hours to obtain copper nanosheets.
[0064] like Figure 8 As shown, it is a transmission electron microscope image of the copper nanosheets prepared in Example 6 of the present invention. Figure 8 As can be seen from the figure, the average side length of the prepared nanosheets is about 360 nm, and they are mainly triangles or hexagons. The yield of the obtained copper nanosheets is 95%.
[0065] Comparative Example 1
[0066] The synthesis method is substantially the same as that of Example 1, except that:
[0067] No etchant was added.
[0068] like Fig. 9 As shown, it is a transmission electron microscope picture of the copper nanocrystal obtained in Comparative Example 1 of the present invention. Fig. 9 It can be seen that the average particle size of the prepared nanocrystals is about 19 nm, mainly in the form of flakes and spherical particles. The yield of the obtained copper nanosheets is only 18%.
[0069] It can be seen from Example 1 and Comparative Example 1 that when the etchant is not used, the obtained product is a mixture of various types of nanocrystals, which further demonstrates the screening effect of the oxidation etching process on the nanosheets.
[0070] Application Example 1
[0071] The copper nanosheets prepared in Example 2 of the present invention are used for the reduction of 4-nitrophenol (4-NP), and the specific process is as follows:
[0072] 2 mL of water, 0.17 mL of 4-NP (1 mM), and 0.28 mL of sodium borohydride (0.1 M) were added to a cuvette and mixed evenly, and then 20 μL of Cu nanosheets or nanospheres (40 mM) were quickly injected into the mixture. No catalyst was added as a blank control, and the reaction spectrum was recorded using a UV-visible spectrometer.
[0073] like Fig.10 As shown in the figure, it can be seen that the 4-NP reduction performance of the obtained ultrathin copper nanosheets is far superior to that of large-size copper nanosheets (J.Ind.Eng.Chem.2022,108,476-483), and 4-NP can be completely reduced within 90 seconds, which is comparable to the catalytic performance of some precious metal gold and silver catalysts (J.Ind.Eng.Chem.2022,108,476,J.Hazard.Mater.2016,310,89,Nanoscale 2020,12,372).
[0074] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A method for preparing copper nanosheets, characterized in that: The method includes: By adding surfactants and ligands to copper salts, the copper salts are reduced to nuclei by a reducing agent. The nuclei serve as seeds for the growth of nanocrystals and non-flaky crystals are etched away during the oxidation etching process of the etchant. The surfactants and ligands passivate the surface of the copper nanosheets to protect the flaky seed crystals of copper, thereby obtaining copper nanosheets.
2. The preparation method according to claim 1, characterized in that: The method includes: Copper salt, surfactant, ligand and etchant are added to the solvent to make the concentration of copper salt in the reaction system 1×10 - 5 mol / L~5×10 -2 mol / L, and then heated to 20-80°C to obtain a mixed solution; Adding a reducing agent to the mixed solution, stirring and reacting for 1 to 3 hours to obtain an ultrathin copper nanosheet; Alternatively, copper salt, surfactant and complexing agent are added to the solvent to make the concentration of copper salt in the reaction system 1×10 -5 mol / L~5×10 -2 mol / L, and then heated to 20-80°C to obtain a mixed solution; Then, an etchant and a reducing agent are added to the mixed solution, and the mixture is stirred for reaction for 1 to 3 hours to obtain an ultra-thin copper nanosheet.
3. The preparation method according to claim 1, characterized in that: The copper salt is selected from any one or more of copper chloride, copper nitrate, copper sulfate, copper acetate, copper formate, copper acetylacetonate and copper hydroxide; Or / and, the surfactant is selected from any one or more of polyvinyl pyrrolidone, hexadecyl ammonium chloride, hexadecyl ammonium bromide and polydiallyl dimethyl ammonium chloride; or / and, the complexing agent is selected from any one or more of diethylamine, ethylenediamine, ethanolamine, propylenediamine, ammonia water and sodium iodide; Or / and, the etchant is selected from any one or more of oxygen, hydrogen peroxide and iodine; Or / and, the reducing agent is selected from any one or more of hydroxylamine, hydroxylamine hydrochloride and hydrazine hydrate.
4. The preparation method according to claim 3, characterized in that: When the etchant is selected from oxygen, oxygen gas is bubbled in to achieve etching.
5. The preparation method according to claim 4, characterized in that: When the oxygen is bubbled at a rate of 150 mL / min, the bubbling time is more than 5 minutes.
6. The preparation method according to claim 1, characterized in that: The solvent is selected from any one or more of water, dimethylformamide and ethylene glycol.
7. The preparation method according to claim 1, characterized in that: The concentration of the surfactant in the mixed solution is 1wt%; The concentration of the complexing agent in the mixed solution is greater than or equal to the concentration of the copper salt; The concentration of the etchant in the mixed solution is 0.1 to 2 times the concentration of the copper salt; The concentration of the reducing agent in the mixed solution is 2 to 10 times the concentration of the copper salt.
8. The copper nanosheet obtained by the preparation method according to any one of claims 1 to 7.
9. The copper nanosheet according to claim 8, characterized in that: The shape of the copper nanosheets includes: triangle and / or hexagon.
10. Use of the copper nanosheets as claimed in claim 8 or 9 in reducing 4-nitrophenol to synthesize 4-aminophenol.
Citation Information
Cited By
Phase and morphology dual-controllable copper-based micro-nano material and homogeneous synthesis method thereof
CN121571665A